Personalized Learning Approaches in Teaching English for Diverse Learners - Siti Meutia Sari (Rahis Cendekia Indonesia, 2025)
The increasing diversity in English language classrooms has prompted the need for more adaptive and individualized teaching methods. This study examines the implementation of personalized learning approaches to accommodate the varying needs, interests, and abilities of learners. Using a qualitative descriptive method, data were collected through observation, interviews, and document analysis from English teachers who employ personalized strategies in their instruction. The results reveal that personalized learning fosters greater student engagement, motivation, and language acquisition by offering differentiated tasks, integrating technology, providing individualized feedback, and conducting formative assessments. However, challenges such as large class sizes, limited resources, and the necessity of strong teacher competencies were also identified. It is concluded that personalized learning can significantly improve the effectiveness of English language education for diverse learners if supported by appropriate institutional policies, continuous professional development, and learner training in self-regulation. The findings offer valuable insights for educators seeking to design more inclusive, responsive, and student-centered English language classrooms.